Emergent contaminants in sediments and fishes from the Tamsui River (Taiwan): Their spatial-temporal distribution and risk to aquatic ecosystems and human health. (March 2020) - Lee, Ching-Chang; Hsieh, Chia-Yi; Chen, Colin S.; Tien, Chien-Jung
Abstract: The occurrence of emergent contaminants, 24 polybrominated diphenyl ethers (PBDEs), di(2-ethylhexyl)phthalate (DEHP), dibutyl phthalate (DBP), butyl benzyl phthalate (BBP), diethyl phthalate (DEP), dimethyl phthalate (DMP), di-n-octyl phthalate (DnOP), bisphenol A (BPA) and nonylphenol (NP), was investigated in sediments and fishes collected from the Tamsui River system to determine the factors that influence their distribution and their risk to aquatic ecosystems and human health. The concentrations of total PBDEs, DEHP, DBP, BBP, DEP, DMP, DnOP, BPA and NP in sediments were 1–955, ND-23570, <50–411, <50–430, ND-80, ND-<50, ND-<50, 1–144, 3–19624 μg/kg dw, respectively. The spatial-temporal distribution trends of these compounds in sediments could be attributed to urbanization, industrial discharge and effluents from wastewater treatment plants. The PBDE congener distribution patterns (BDE-209 was the dominant congener) in sediments reflected the occurrence of debromination of BDE-209 and the elution of penta-BDE from the treated products. The concentrations of total PBDEs, DEHP, DBP, BBP, DEP, DMP, DnOP, BPA and NP in fish muscles were 2–66, 17–1046, <10–231, <10–66, <30, ND-<30, ND-<30, 0.4–7 and 3–440 μg/kg ww, respectively. The species-specific bioaccumulation of these compounds by fish was found and four species particularly showed high bioaccumulation potential. BDE-47 was the predominant BDE congener in fish muscles, suggesting high bioavailability and bioaccumulation of this compound. The results of biota–sediment accumulation factors showed that BDE-47, 99, 100, 153 and 154 had relatively high bioavailability and bioaccumulation potential for some fish species. The ecological risk assessment showed that the concentrations of BPA and NP in sediments were likely to have adverse effects on aquatic organisms (risk quotients > 1). The human health risk assessment according to hazard quotients (HQs) and carcinogenic risks (CRs) revealed no remarkable risk to human health through consumption of fish contaminated with BDE-47, 99, 100, 154, 209, DEHP, BPA and NP. Graphical abstract: Image 1 Highlights: Urbanization caused high levels of PBDEs, phthalates, BPA and NP in sediments/fish. The concentrations of contaminants in sediments showed a seasonal variation. BSAF results indicated fish had high accumulation potential to lower BDE congeners. BPA and NP in sediments were likely to have adverse effects on aquatic organisms. Consumption of PBDEs/DEHP/BPA/NP-contaminated fish posed no risks to human health. Abstract : Occurrence and risk of emergent contaminants.